The Use of Instagram as a Social Media Platform for Learning Arabic (Content Analysis on Instagram Account @itaf.id) - Rahman, Batsyan Jundur; Saleh, Nalahuddin; Nurbayan, Yayan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The rapid development of digital technology and the use of social media in this 4.0 era has made social media a primary need for society, one of which is the Instagram application. Instagram is used by its users to share moments in the form of photos or videos. The purpose of this research is to show Instagram users that this platform has other benefits, namely as an easier and more efficient means of learning Arabic The approach used in this research is a qualitative method, where the researcher acts as the main instrument in data collection. The researcher is tasked with understanding the context and analyzing the information obtained from the @itaf.id Instagram account. The main technique applied in data collection is content analysis, which includes an examination of the verbal and visual data available on the social media platform. This article will review the utilization of @itaf.id Instagram account as a medium in Arabic language learning. In addition, this study will also identify the various advantages and limitations of Instagram as an educational tool in supporting the Arabic language learning process in a more interactive and visual-based manner.